Strategis dan Efektifitas Pengendalian Hama Penggerek Buah Kakao di Kecamatan Kodeoha Kabupaten Kolaka Utara - Rachmani, Muhammad Kaisar Prakarsa; Akmal; Naima Haruna (SINTA Journal (Science, Technology, and Agricultural), 2025)
The threat of cocoa fruit borer pests (Conopomorpha cramerella) has caused a significant decrease in cocoa productivity in Indonesia. The massive use of synthetic insecticides by farmers has a negative impact on the environment and products. This study aims to formulate an effective and sustainable integrated pest control strategy for cocoa plants in Kodeoha District, North Kolaka Regency, Indonesia. Qualitative and quantitative descriptive research methods were used, with the data analyzed using regression analysis to measure yield loss and SWOT analysis to formulate control strategies. The results show that the most appropriate control strategy is the Grow and Build strategies, which focus on the utilization of internal strengths and external opportunities. This strategy includes increasing the capacity of farmers, providing adequate facilities and infrastructure, and increasing training and mentoring. The implementation of this strategy, combined with the latest control technologies such as biological agents and pheromones, is expected to increase farmers' independence and ensure the sustainability of cocoa production.